Climate change and rubber production: Risks scenarios and research needs for adaptation - Gohet, E.; Francois, Y; Cauchy, T.; Gay, F. (Proceedings of the IRRDB International Rubber Conference 2023, 20-21 February 2023, IRRDB, Kuala Lumpur, Malaysia, pp. 2-10.)
The Composite Climatic Marginality (CCM Index) describes the type and intensity of the climatic marginality for rubber production obtained from Hevea brasiliensis and estimates the corresponding losses of latex yield due to different types of marginal climates. Depending on the different climate change (CC) scenarios established by the Intergovernmental Panel on Climate Change (IPCC), the forecasted evolution of the CCM Index can be calculated to estimate and map, at world, region, country or province levels, the possible effects of climate change on rubber production until 2100. The major effect of CC on rubber should likely be due to the rise in temperature (min, max and mean), as the average annual temperature in current rubber growing areas will exceed 28oC, the current observed maximum threshold for rubber cultivation. The CC will also result in variations of rainfall patterns and increased frequencies of extreme climatic events such as storms, increasing the risk of wind damage, flooding and tapping disruption. These forecasted modifications of climate may as well favour the emergence of new pests or pathogens or increase susceptibility to those currently existing. Under any IPCC scenario, rubber production will likely be negatively affected through photosynthesis and water uptake dysfunction due to an increased vapor pressure deficit (VPD) affecting latex regeneration and flow. A few areas currently characterized by a rather cold climate are scarce and will mainly remain climatically marginal due to long dry seasons. This is likely to favour land use changes. Globally, the rubber growing areas without climate limitations will likely be drastically reduced. The current study presents the forecasted effects of CC on rubber production throughout the 21st century in some of the main rubber production regions or countries, depending on different IPCC scenarios. It emphasizes the urgency to engage the global rubber research agencies on the adaptation to CC (ecophysiology studies and development of climate smart agricultural practices, including clonal selection).
Keywords: Climate change; Climate smart agriculture; Good agricultural practices; IPCC; Rubber Production